2014
DOI: 10.1158/1535-7163.mct-13-0481
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Acquired BRAF Inhibitor Resistance in Melanoma via Targeted Inhibition of Hsp90 with Ganetespib

Abstract: Activating BRAF kinase mutations serve as oncogenic drivers in over half of all melanomas, a feature that has been exploited in the development of new molecularly targeted approaches to treat this disease. Selective BRAF V600E inhibitors, such as vemurafenib, typically induce initial, profound tumor regressions within this group of patients; however, durable responses have been hampered by the emergence of drug resistance. Here, we examined the activity of ganetespib, a small-molecule inhibitor of Hsp90, in me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 32 publications
4
81
0
Order By: Relevance
“…6, A and B) as already indicated by array analysis (Fig. 2, A and B) (34,37,63). Consistent with an aurin-induced up-regulation of heat shock response gene expression downstream of PCR; n ϭ 3).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…6, A and B) as already indicated by array analysis (Fig. 2, A and B) (34,37,63). Consistent with an aurin-induced up-regulation of heat shock response gene expression downstream of PCR; n ϭ 3).…”
Section: Discussionsupporting
confidence: 84%
“…Small molecule inhibitors of Hsp90 are, therefore, an important class of experimental and investigational chemotherapeutics that have reached the stage of clinical testing. Hsp90-directed inhibitory activity of aurin seems to be of particular relevance in the context of melanoma chemotherapy, as Hsp90 inhibition has emerged as a particularly promising therapeutic strategy based on the finding that V600E B-Raf is an obligatory Hsp90 client protein essential to the clonal evolution of melanoma tumors and that Hsp90 inhibitors cause the degradation of V600E B-Raf (34,37,63). Moreover, it has now been observed that V600E BRAF melanoma cells that have acquired resistance to vemurafenib due to a variety of molecular changes retain sensitivity to Hsp90 inhibition suggesting feasibility of FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we now report that very modest, sustained inhibition of HSP90, at well-tolerated levels that do not deplete clients on their own or activate HSF1, reduces heterogeneity in the response of tumors to antiestrogens and prolongs the duration of disease control by these agents. Focusing on these striking effects of low-level, noncytotoxic HSP90 inhibition, the current study provides a new perspective, one very different from the many previous reports describing interesting activity for high-level HSP90 inhibition against recurrent drug-resistant cancers (33)(34)(35)(36) or synergistic interaction with other chemotherapeutics to increase their activity (37)(38)(39). From a translational perspective, the recent development of orally bioavailable HSP90 inhibitors should make sustained, low-level inhibitor exposure feasible in patients.…”
mentioning
confidence: 92%
“…In the melanoma setting, DNA-RP (such as ATR, MRN complex proteins (MRE11, Rad50, NBN), Rad51, PRKDC) are transcriptionally over expressed in a disease stage-associated manner in association with chemotherapy-resistance and poor overall survival [11][12][13][14][15][16][17][18]. Notably, tumor cell (over) expression of DNA-RP may also be posttranslationally stabilized via the action of heat shock protein-90 HSP90; [11,[13][14][15][16][17]19], a molecular chaperone that is highlyabundant in the cancer proteome [20]. HSP90 forms the core of a super-chaperone machine consisting of HSP70, HSP40, HIP and HOP, which extends the molecular lifespan of a growing list of client proteins, including signaling protein kinases, transcription factors, DNA-RP and other cytosolic or nuclear proteins in their functionally mature and active conformations [19].…”
mentioning
confidence: 99%